If ${z_1}$ is a complex number other than $ - 1$ such that $\left| {{z_1}} \right| = 1$ and ${z_2} = \dfrac{{{z_1} - 1}}{{{z_1} + 1}}$, then show that the real parts of ${z_2}$ is zero.
Answer
Verified
439.2k+ views
Hint: As in the question we have given ${z_1}$ is a complex number let’s consider ${z_1} = x + iy$ where $x$ is real part and $iy$ is imaginary part. Using all the given conditions which are given in the question we can find the ${z_2}$ and arrive at the required answer.
Complete step by step answer:
Here in this question we have given that ${z_1}$ is a complex number, so we can write ${z_1}$ as ${z_1} = x + iy$ where $x$ is real part and $iy$ is imaginary part.
As we have given $\left| {{z_1}} \right| = 1$ we can write as below.
$\left| {{z_1}} \right| = 1$
$ \Rightarrow \sqrt {{x^2} + {y^2}} = 1$
Squaring on both the sides and simplifying, we get
$ \Rightarrow {x^2} + {y^2} = 1$
Also we have given ${z_1} \ne - 1$
$ \Rightarrow x + iy \ne - 1$
$ \Rightarrow x \ne - 1$
Now, they have asked to show the real part of ${z_2}$ is zero in the expression ${z_2} = \dfrac{{{z_1} - 1}}{{{z_1} + 1}}$.
Now, in the above expression of ${z_2}$ replace ${z_1} = x + iy$ and simplify the expression. Therefore, we get
${z_2} = \dfrac{{\left( {x + iy} \right) - 1}}{{\left( {x + iy} \right) + 1}}$
The above expression can be written as below, for the simplification purpose.
$ \Rightarrow {z_2} = \dfrac{{\left( {x - 1} \right) + iy}}{{\left( {x + 1} \right) + iy}}$
Now multiply and divide the above expression by conjugate of the value, which is as below.
$ \Rightarrow {z_2} = \dfrac{{\left( {x - 1} \right) + iy}}{{\left( {x + 1} \right) + iy}} \times \dfrac{{\left( {x - 1} \right) - iy}}{{\left( {x + 1} \right) - iy}}$
Now, we simplify the above expression. We get
$ \Rightarrow {z_2} = \dfrac{{\left( {x - 1} \right)\left( {x + 1} \right) - \left( {x - 1} \right)y.i + \left( {x + 1} \right)y.i - {y^2}{i^2}}}{{{{\left( {{x^2} + 1} \right)}^2} - {{\left( {iy} \right)}^2}}}$
$ \Rightarrow {z_2} = \dfrac{{\left( {x - 1} \right)\left( {x + 1} \right) - \left( {x - 1} \right)y.i + \left( {x + 1} \right)y.i - {y^2}{i^2}}}{{{{\left( {{x^2} + 1} \right)}^2} - {{\left( {iy} \right)}^2}}}$
Now, simplify the above expression by separating the real and imaginary terms, we write as
$ \Rightarrow {z_2} = \dfrac{{\left( {{x^2} - 1 + {y^2}} \right) + i\left( { - xy + y + xy + y} \right)}}{{{{\left( {x + 1} \right)}^2} + {y^2}}}$ (we know ${i^2} = - 1$)
$ \Rightarrow {z_2} = \dfrac{{\left( {{x^2} + {y^2} - 1} \right) + 2iy}}{{{{\left( {x + 1} \right)}^2} + {y^2}}}$
By using the condition which we have ${x^2} + {y^2} = 1$ in the above equation, we get
$ \Rightarrow {z_2} = \dfrac{{\left( {1 - 1} \right) + 2iy}}{{{{\left( {x + 1} \right)}^2} + {y^2}}}$
$ \Rightarrow {z_2} = \dfrac{{2iy}}{{{{\left( {x + 1} \right)}^2} + {y^2}}}$
The above expression can be written as
$ \Rightarrow {z_2} = 0 + i.\dfrac{{2y}}{{{{\left( {x + 1} \right)}^2} + {y^2}}}$
In the above expression we have the real part as $0$ and the imaginary part as $i.\dfrac{{2y}}{{{{\left( {x + 1} \right)}^2} + {y^2}}}$.
Hence we have proved that the real parts of ${z_2}$ are zero.
Note:
Whenever we have this type of problem, first we need to consider complex values and then when it comes to the simplification part, it’s very important to be careful while solving using the conjugate values of the corresponding values. If you fail to take the correct conjugate values then you may end up with the wrong answer.
Complete step by step answer:
Here in this question we have given that ${z_1}$ is a complex number, so we can write ${z_1}$ as ${z_1} = x + iy$ where $x$ is real part and $iy$ is imaginary part.
As we have given $\left| {{z_1}} \right| = 1$ we can write as below.
$\left| {{z_1}} \right| = 1$
$ \Rightarrow \sqrt {{x^2} + {y^2}} = 1$
Squaring on both the sides and simplifying, we get
$ \Rightarrow {x^2} + {y^2} = 1$
Also we have given ${z_1} \ne - 1$
$ \Rightarrow x + iy \ne - 1$
$ \Rightarrow x \ne - 1$
Now, they have asked to show the real part of ${z_2}$ is zero in the expression ${z_2} = \dfrac{{{z_1} - 1}}{{{z_1} + 1}}$.
Now, in the above expression of ${z_2}$ replace ${z_1} = x + iy$ and simplify the expression. Therefore, we get
${z_2} = \dfrac{{\left( {x + iy} \right) - 1}}{{\left( {x + iy} \right) + 1}}$
The above expression can be written as below, for the simplification purpose.
$ \Rightarrow {z_2} = \dfrac{{\left( {x - 1} \right) + iy}}{{\left( {x + 1} \right) + iy}}$
Now multiply and divide the above expression by conjugate of the value, which is as below.
$ \Rightarrow {z_2} = \dfrac{{\left( {x - 1} \right) + iy}}{{\left( {x + 1} \right) + iy}} \times \dfrac{{\left( {x - 1} \right) - iy}}{{\left( {x + 1} \right) - iy}}$
Now, we simplify the above expression. We get
$ \Rightarrow {z_2} = \dfrac{{\left( {x - 1} \right)\left( {x + 1} \right) - \left( {x - 1} \right)y.i + \left( {x + 1} \right)y.i - {y^2}{i^2}}}{{{{\left( {{x^2} + 1} \right)}^2} - {{\left( {iy} \right)}^2}}}$
$ \Rightarrow {z_2} = \dfrac{{\left( {x - 1} \right)\left( {x + 1} \right) - \left( {x - 1} \right)y.i + \left( {x + 1} \right)y.i - {y^2}{i^2}}}{{{{\left( {{x^2} + 1} \right)}^2} - {{\left( {iy} \right)}^2}}}$
Now, simplify the above expression by separating the real and imaginary terms, we write as
$ \Rightarrow {z_2} = \dfrac{{\left( {{x^2} - 1 + {y^2}} \right) + i\left( { - xy + y + xy + y} \right)}}{{{{\left( {x + 1} \right)}^2} + {y^2}}}$ (we know ${i^2} = - 1$)
$ \Rightarrow {z_2} = \dfrac{{\left( {{x^2} + {y^2} - 1} \right) + 2iy}}{{{{\left( {x + 1} \right)}^2} + {y^2}}}$
By using the condition which we have ${x^2} + {y^2} = 1$ in the above equation, we get
$ \Rightarrow {z_2} = \dfrac{{\left( {1 - 1} \right) + 2iy}}{{{{\left( {x + 1} \right)}^2} + {y^2}}}$
$ \Rightarrow {z_2} = \dfrac{{2iy}}{{{{\left( {x + 1} \right)}^2} + {y^2}}}$
The above expression can be written as
$ \Rightarrow {z_2} = 0 + i.\dfrac{{2y}}{{{{\left( {x + 1} \right)}^2} + {y^2}}}$
In the above expression we have the real part as $0$ and the imaginary part as $i.\dfrac{{2y}}{{{{\left( {x + 1} \right)}^2} + {y^2}}}$.
Hence we have proved that the real parts of ${z_2}$ are zero.
Note:
Whenever we have this type of problem, first we need to consider complex values and then when it comes to the simplification part, it’s very important to be careful while solving using the conjugate values of the corresponding values. If you fail to take the correct conjugate values then you may end up with the wrong answer.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
The reservoir of dam is called Govind Sagar A Jayakwadi class 11 social science CBSE
10 examples of friction in our daily life
Difference Between Prokaryotic Cells and Eukaryotic Cells
State and prove Bernoullis theorem class 11 physics CBSE
Proton was discovered by A Thomson B Rutherford C Chadwick class 11 chemistry CBSE
State the laws of reflection of light